Regulation of Smooth Muscle Cell Proliferation by NADPH Oxidases in Pulmonary Hypertension - John C. Huetsch; Karthik Suresh; Larissa A. Shimoda (MDPI AG, 2019)
Hyperproliferation of pulmonary arterial smooth muscle cells is a key component of vascular remodeling in the setting of pulmonary hypertension (PH). Numerous studies have explored factors governing the changes in smooth muscle cell phenotype that lead to the increased wall thickness, and have identified various potential candidates. A role for reactive oxygen species (ROS) has been well documented in PH. ROS can be generated from a variety of sources, including mitochondria, uncoupled nitric oxide synthase, xanthine oxidase, and reduced nicotinamide adenine dinucleotide phosphate (NADPH) oxidase. In this article, we will review recent data supporting a role for ROS generated from NADPH oxidases in promoting pulmonary arterial smooth muscle cell proliferation during PH.